Parasitism by Sphincterodiplostomum musculosum (Digenea, Diplostomidae) metacercariae in the eyes of Steindachnerina insculpta (Characiformes, Curimatidae) - Brandão,Heleno (2014)
New occurrences and effects of parasitism by metacercariae in fish eyes have recently been discussed in many studies. The aim of the present study was to evaluate the infection levels of the eye flukes Sphincterodiplostomum musculosumDubois, 1936 (metacercariae) in Steindachnerina insculpta (Fernádez-Yépez, 1948) from three ecosystems under the influence of the Jurumirim reservoir (Paranapanema, Taquari and Veados Rivers). A total of 174 fish specimens were sampled between April 2011 and April 2012. There were high levels of infection by S. musculosum metacercariae in the eyes of S. insculpta from all the sampled ecosystems, thus presenting broad geographical distribution. The histological analyses revealed that the metacercariae were apparently lodged behind the retina. The smaller fish from the Taquari River were less parasitized by metacercariae than the adults. This pattern can be explained by the cumulative effect of parasitism, as demonstrated by the positive correlation between the abundance of metacercariae and fish body size.